Randomised controlled trial of transanal endoscopic microsurgery versus endoscopic mucosal resection for large rectal adenomas (TREND Study). Issue 5 (28th June 2017) - Barendse, Renée M; Musters, Gijsbert D; de Graaf, Eelco J R; van den Broek, Frank J C; Consten, Esther C J; Doornebosch, Pascal G; Hardwick, James C; de Hingh, Ignace H J T; Hoff, Chrisiaan; Jansen, Jeroen M; van Milligen de Wit, A W Marc; van der Schelling, George P; et al.
Abstract : Objective: Non-randomised studies suggest that endoscopic mucosal resection (EMR) is equally effective in removing large rectal adenomas as transanal endoscopic microsurgery (TEM), but EMR might be more cost-effective and safer. This trial compares the clinical outcome and cost-effectiveness of TEM and EMR for large rectal adenomas. Design: Patients with rectal adenomas ≥3 cm, without malignant features, were randomised (1:1) to EMR or TEM, allowing endoscopic removal of residual adenoma at 3 months. Unexpected malignancies were excluded postrandomisation. Primary outcomes were recurrence within 24 months (aiming to demonstrate non-inferiority of EMR, upper limit 10%) and the number of recurrence-free days alive and out of hospital. Results: Two hundred and four patients were treated in 18 university and community hospitals. Twenty-seven (13%) had unexpected cancer and were excluded from further analysis. Overall recurrence rates were 15% after EMR and 11% after TEM; statistical non-inferiority was not reached. The numbers of recurrence-free days alive and out of hospital were similar (EMR 609±209, TEM 652±188, p=0.16). Complications occurred in 18% (EMR) versus 26% (TEM) (p=0.23), with major complications occurring in 1% (EMR) versus 8% (TEM) (p=0.064). Quality-adjusted life years were equal in both groups. EMR was approximately €3000 cheaper and therefore more cost-effective. Conclusion: Under the statistical assumptions of this study, non-inferiority of EMR could not be demonstrated. However, EMR may have potential as the primary method of choice due to a tendency of lower complication rates and a better cost-effectiveness ratio. The high rate of unexpected cancers should be dealt with in further studies.